Anti-hyperglycemic potential of alginate oligosaccharide in a high glucose-induced zebrafish model. (July 2022) - Kim, Hyo Hee; Vaidya, Bipin; Cho, Se-Young; Kwon, Joseph; Kim, Duwoon
Graphical abstract: Highlights: AOS exhibits anti-hyperglycemic activity in high-glucose induced hyperglycemic zebrafish. AOS reduces lactic acid level in hyperglycemic zebrafish. AOS induces glucose oxidation by enhancing PDHA1 activity via reducing PDK2. AOS reduces high glucose-induced mortality, oxidative stress and apoptosis. Abstract: The anti-hyperglycemic activity of alginate oligosaccharide (AOS) and its mechanism were elucidated in a hyperglycemic zebrafish model. The model was prepared by inducing high glucose in zebrafish for the study. AOS treatment significantly reduced blood glucose level and delayed mortality in hyperglycemic zebrafish. To explain the anti-hyperglycemic mechanism of AOS, a comparative proteomic analysis was performed in three groups (control, hyperglycemic, AOS-treated hyperglycemic) of zebrafish. Among 639 identified proteins, 72 proteins modulated by AOS treatment were classified into key biofunctional categories, including energy metabolism and survival. Ingenuity pathway analysis predicted that AOS treatment inhibits lactic acid production by suppressing hypoxia inducible factor 1 subunit a (HIF1A) via modulating insulin receptor (INSR), sirtuin 1 (SIRT1) and lactate dehydrogenase A (LDHA); and induces glucose oxidation by enhancing pyruvate dehydrogenase 1 (PDHA1) via decreasing pyruvate dehydrogenase kinase isoform 2 (PDK2). Subsequently, RT-qPCR analysis verified the reduction of hif1a, pdk2 and ldha gene expression, and the elevation of insr and sirt1 expression by AOS treatment in hyperglycemic zebrafish. In conclusion, AOS could be an alternative therapeutic agent to ameliorate hyperglycemia by stimulating glucose oxidation and suppressing lactic acid pathway.